Quantifying the rate and predictors of occult lymph node involvement in patients with clinically node-negative non-small cell lung cancer. (3rd April 2022) - Haque, Waqar; Singh, Anukriti; Park, Henry S.; Teh, Bin S.; Butler, E. Brian; Zeng, Ming; Lin, Steven H.; Welsh, James W.; Chang, Joe Y.; Verma, Vivek
Abstract: Purpose: It is essential to evaluate the risk of occult lymph node (LN) disease in early-stage non-small cell lung cancer (NSCLC), especially because delivering stereotactic ablative radiotherapy (SABR) assumes no occult spread. This study was designed to assist clinicians in roughly quantifying this risk for cN0 NSCLC. Methods: The National Cancer Data Base was queried for cN0 cM0 lung squamous cell or adenocarcinoma who underwent surgery and LN dissection without neoadjuvant therapy. Statistics included multivariable logistic regression to evaluate factors associated with pN + disease. Results: 109, 964 patients were included. For tumors with size ≤1.0, 1.1–2.0, 2.1–3.0, 3.1–4.0, 4.1–5.0, 5.1–6.0, 6.1–7.0, and >7.0 cm, the pN + rate was 4.4, 7.7, 12.9, 18.0, 20.2, 22.5, 24.4, and 26.4%, respectively. When examining patients with more complete LN dissections (defined as removal of at least 10 LNs), the respective values were 6.6, 11.5, 17.6, 25.3, 26.8, 29.7, 30.7, and 31.6%. Moderately-poorly differentiated disease and adenocarcinomas were associated with a higher rate of pN + disease ( p  < .001 for both). For every cm increase in tumor size, the relative occult nodal risk increased by 10–14% ( p  < .001). For every elapsed day from initial diagnosis, the relative risk increased by ∼1% ( p  < .001). Graphs with best-fit lines were created based on tumor size, histology, and differentiation to aid physicians in estimating the pN + risk. Conclusions: This nationwide study can allow clinicians to roughly estimate the rate of occult LN disease in cN0 NSCLC. These data can also assist in guiding enrollment on randomized trials of SABR ± immunotherapy, individualizing follow-up imaging surveillance, and patient counseling to avoid post-diagnosis delays.